Key Determinants for Marketing and Operational Strategies of Hotel Business - Alias, Anuar; Be Tan, Sok (Journal of Surveying, Construction and Property, 2014)
The main goal of this research is to identify the key determinants on marketing and operational strategies for hotels in the Klang Valley through a study and review of feedback gathered from stakeholders – hotel guests and hotel operators. This research adopted the mixed method of quantitative and qualitative approaches to achieve the objectives. The findings of this research revealed that the top five (5) determinants which are perceived to be of greatest importance in determining the purchase behaviour of hotel guests, and the key determinants of hotels as measured by average room rate. Among the top five (5) determinants, scale, location and service quality were found to be significant variables. The results of this research were largely consistent with the outcome of research conducted by researchers in other publication. It is envisaged that these research findings would be of great interests especially to the hoteliers in devising their marketing and operational strategies such that sufficient focus is given to the key determinants which are of particular importance to hotel guests in driving their decision to select a hotel room.